Analisis Pengaruh Penggunaan Marketplace Terhadap Peningkatan Penjualan UMKM Tinjauan Menggunakan Metode Systematic Literature Review: Analysis of the Influence of Marketplace Use on Increasing MSME Sales: A Review Using the Systematic Literature Review Method - Chandini, ANGGELLA; Jhon Veri (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2025)
This research applies the Systematic Literature Review (SLR) method to analyze the impact of using the marketplace on increasing sales of Micro, Small and Medium Enterprises (MSMEs). This research collected two types of data, namely primary data and secondary data. References or reference materials were made through Garda Rujukan Digital (GARUDA). After going through the screening process, seven journals relevant to the research topic were found. Based on a review of nine articles published between 2019 and 2024, it was found that marketplace utilization plays an important role in expanding market reach, increasing product exposure, and simplifying the transaction process for customers. In addition, optimizing digital marketing strategies through marketplaces contributes to building customer loyalty and increasing the operational efficiency of MSMEs.  These findings highlight the urgency of implementing effective strategies in utilizing and managing marketplaces to support sustainable business growth and strengthen MSME competitiveness in the digital era. Furthermore, this study identifies that aspects such as service quality, customer trust, and innovation in promotional strategies influence the success of MSMEs in utilizing the marketplace. The use of integrated social media and data analysis allows MSMEs to understand consumer behavior and develop more targeted marketing strategies.  Although the marketplace offers various opportunities, there are still a number of obstacles such as the high level of competition, the cost of using the platform, and the limited digital literacy faced by some MSME players. Therefore, support is needed from various stakeholders, including the government, platform providers, and educational institutions, in the form of training, mentoring, and wider access to digital technology. Thus, MSMEs can optimize the use of marketplaces to achieve sustainable business growth and increase competitiveness in the global market.